Flexible Hybrid Sensors for Health Monitoring: Materials and Mechanisms to Render Wearability. Issue 15 (24th July 2019) - Gao, Yuji; Yu, Longteng; Yeo, Joo Chuan; Lim, Chwee Teck
Abstract: Wearable electronics have revolutionized the way physiological parameters are sensed, detected, and monitored. In recent years, advances in flexible and stretchable hybrid electronics have created emergent properties that enhance the compliance of devices to our skin. With their unobtrusive attributes, skin conformable sensors enable applications toward real‐time disease diagnosis and continuous healthcare monitoring. Herein, critical perspectives of flexible hybrid electronics toward the future of digital health monitoring are provided, emphasizing its role in physiological sensing. In particular, the strategies within the sensor composition to render flexibility and stretchability while maintaining excellent sensing performance are considered. Next, novel approaches to the functionalization of the sensor for physical or biochemical stimuli are extensively covered. Subsequently, wearable sensors measuring physical parameters such as strain, pressure, temperature, as well as biological changes in metabolites and electrolytes are reported. Finally, their implications toward early disease detection and monitoring are discussed, concluding with a future perspective into the challenges and opportunities in emerging wearable sensor designs for the next few years. Abstract : Flexible hybrid sensors for health sensing and strategies to render wearability are reviewed. Configurations of sensor composition (substrates, interconnects, and sensing elements) for robust performance in wearable applications are illustrated. Emerging approaches in health monitoring in the physical and biochemical domains are discussed. Finally, a future perspective for wearable sensor technology is presented.